2018
DOI: 10.1186/s40643-018-0202-z
|View full text |Cite
|
Sign up to set email alerts
|

Improved methanol-derived lovastatin production through enhancement of the biosynthetic pathway and intracellular lovastatin efflux in methylotrophic yeast

Abstract: Background: Methanol has attracted interest as a substrate for improvement of product titers and yields of bioprocesses, because methanol has a more reduced state than sugars do and can be renewably synthesized from abundant natural gas supplies. Our aim was to engineer methylotrophic Pichia pastoris to convert methanol into value-added lovastatin more productively. Results:A strengthened biosynthetic pathway of lovastatin was constructed through the assembly of three modules with increasing module-specific an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 23 publications
(39 reference statements)
0
22
0
Order By: Relevance
“…Also, heterologous expression of a homolog of MlcE did not trigger increased resistance to LV in a LV-sensitive strain Aspergillus nidulans (Hutchinson et al 2000). Differently, our previous work revealed that a homolog (TapA) of MlcE from A. terreus promoted LV release and improved LV production by a methanol-utilizing yeast Komagataella phaffii (syn Pichia pastoris) (Liu et al 2018a).…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…Also, heterologous expression of a homolog of MlcE did not trigger increased resistance to LV in a LV-sensitive strain Aspergillus nidulans (Hutchinson et al 2000). Differently, our previous work revealed that a homolog (TapA) of MlcE from A. terreus promoted LV release and improved LV production by a methanol-utilizing yeast Komagataella phaffii (syn Pichia pastoris) (Liu et al 2018a).…”
Section: Introductionmentioning
confidence: 88%
“…K. phaffii GS115 was purchased from Invitrogen and used for construction of expression strains. J#9 and GS-P GAP -TapA strains were constructed and stored in our laboratory (Liu et al 2018a). The linearized vector was assembled with different fragments by ClonExpress ™ II One Step Cloning Kit (Vazyme Biotech Co., Ltd., China), generating various target plasmids.…”
Section: Construction Of Plasmids and Strainsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, through enhancement of intracellular lovastatin efflux by overexpression of TapA , a putative efflux pump protein from the native lovastatin‐producing strain A. terreus , increment of lovastatin production was achieved with 419 mg L −1 of lovastatin produced using a monoculture fermentation. [ 46 ] In another study, citrinin production pathway was expressed in P. pastoris . Citrinin is regarded as a model compound to explore the potential for synthesis polyketides.…”
Section: Production Of Platform Chemicals and Natural Productsmentioning
confidence: 99%